PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERBANKAN DENGAN SIZE DAN LEVERAGE RATIO SEBAGAI VARIABEL PEMODERASI - Elok Fitriya; Lilis Setyorini (Jurnal Ilmiah Akuntansi Indonesia, 2019)
Abstract: Research on CSR on company performance has been carried out both in Indonesia and in other countries. Research that investigates the relationship between CSR and company performance covering financial performance and economic performance is done by Mahoney, et al (2003) who examined the relationship between social performance and corporate environment with financial performance (return on equity / ROE and return on assets / ROA) with debt assets ratio and assets control variables. Disclosure of environmental, social and economic performance in the annual report is to reflect the level of accountability, responsibility and corporate transparency to investors and other stakeholders. The disclosure aims to establish a good and effective communication relationship between the company and the public and other stakeholders about how the company has integrated CSR, namely: environmental and social in every aspect of its operations (Novita and Djakman, 2008). Research will be carried out in Islamic banking listed on the Indonesia Stock Exchange. Observations were made on the Islamic banking financial statements for the period 2015-2018. This research is expected to provide contributions in scientific research journal publications. In addition, it can provide benefits to help sharia banking managers in providing the right decisions. The research results show that Corporate Social Responsibility has no significant effect on the Company's Financial Performance. The company's size and leverage ratio also cannot moderate the relationship of the influence between Corporate Social Responsibility and the Company's Financial Performance.Keywords    : CSR, Company Size, Leverage Ratio, Performance Finance